Adoption and Usage of Generative Artificial Intelligence (GenAI) Tools Among Bandar Penawar MARA Professional College Students (Innovative Teaching and Learning Journal, 2025)
Students’ experiences with generative artificial intelligence (GenAI) tools such as ChatGPT, Canva AI, and Google Gemini vary widely. While some students at Bandar Penawar MARA Professional College (MPC) find these tools helpful for completing assignments and improving academic performance, others remain cautious, particularly regarding data privacy issues, ethics, and over-reliance. This study aims (i) to explore the adoption of GenAI tools among Bandar Penawar MPC students, (ii) to examine how these tools influence learning engagement and academic outcomes, and (iii) to assess students’ concerns and satisfaction regarding GenAI usage in education. Using a quantitative approach with a structured questionnaire, data were collected from 140 diploma students across various semesters. The results show that 97.9% of students are familiar with GenAI tools and 95% actively use them for academic tasks. Most students agree that these tools enhance understanding (82%), save time (52.6%), and make studying enjoyable (77.4%). However, 74.4% of respondents express privacy concerns, and 81.2% agree that GenAI should be used cautiously in academic settings. In conclusion, while GenAI tools are becoming integral to students’ learning routines, there is a clear need for institutional policies and guidelines to ensure responsible and ethical usage.
Keywords: Generative Artificial Intelligence; Academic Engagement; Learning Impact; Privacy Concerns; Ethical Use; MARA Professional College